Program Pemeriksaan Kesehatan Gigi Dan Mulut Melalui Peningkatan Pengetahuan Kesehatan Gigi Masyarakat Di Wilayah Kerja Puskesmas Pate’ne Kab. Maros - Wijayanti, Lumastari Ajeng; Ekawati, Nur; Mayangsari, Nino; Prastyo, Eko; Wahyuni, Sri; Setiawati, Herautami Caezar Yulia; Hilmiah, Hilmiah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
One important part of body health is teeth and mouth. Teeth in the mouth are one of the organs of the body that have several functions, thus oral dental health is an integral part of overall health. The purpose of the study was an effort to reduce the number of caries in oral and dental health by increasing public knowledge in the work area of ​​the Pate'ne Health Center, Maros Regency. The research method was in-depth interviews and surveys using questionnaires regarding the knowledge of oral and dental health in the work area of ​​the Pate'ne Health Center, Maros Regency and by determining the priority of alternative problem solving using the Multiple Criteria Utility Assessment method. Results Knowledge increased from 75.3% to 94.5%. After being carried out through dental and oral health examinations through increasing public dental health knowledge. The conclusion of the study shows that efforts to improve dental and oral health through increasing public dental health knowledge is a very important activity in helping to maintain a person's dental and oral health.